In vivo Hepatoprotective and in vitro Radical Scavenging Activities of Extracts of Rumex abyssinicus Jacq. Rhizome - Adamu BA; Emiru YK; Sintayehu B; Araya EM; Periasamy G; Gebrelibanos Hiben M (Dove Medical Press, 2020)
Betelhem Anteneh Adamu,1,2 Yohannes Kelifa Emiru,1 Biruk Sintayehu,3 Ephrem Mebrhatu Araya,4 Gomathi Periasamy,2 Mebrahtom Gebrelibanos Hiben2 1Department of Pharmacognosy, School of Pharmacy, College of Medicine and Health Sciences, University of Gondar, Gondar, Ethiopia; 2Department of Pharmacognosy, School of Pharmacy, College of Health Sciences, Mekelle University, Mekelle, Ethiopia; 3Department of Pharmaceutical Chemistry and Pharmacognosy, School of Pharmacy, College of Health Sciences, Addis Ababa University, Addis Ababa, Ethiopia; 4Department of Pharmacy, College of Medicine and Health Sciences, Adigrat University, Adigrat, EthiopiaCorrespondence: Ephrem Mebrhatu ArayaDepartment of Pharmacy, College of Medicine and Health Sciences, Adigrat University, P.O. Box 50, Adigrat, EthiopiaTel +251 914425760Email ephremcfc@gmail.comBackground: Liver diseases contribute a prominent global burden of mortality and morbidity. The current therapies of liver diseases have numerous limitations including severe adverse effects. This denotes that new more effective, safer, and cheaper drugs are required and medicinal plants used in traditional medicines often offer ideal opportunities. Accordingly, the present study aimed to evaluate the in vivo hepatoprotective and in vitro radical scavenging activities of dried rhizome extracts of Rumex abyssinicus (R. abyssinicus), which is traditionally claimed to provide hepatoprotection.Materials and Methods: Hepatoprotective activity of extracts was evaluated using carbon tetrachloride (CCl4)-induced liver injury in mice. Pre- and post-treatment models were employed to test the effect of the extracts and silymarin (standard drug). Serum biochemical markers and liver histopathology were used as parameters to evaluate hepatoprotective activities whereas in vitro radical scavenging activity was tested by 2, 2-diphenyl-2-picrylhydrazyl hydrate (DPPH) assay.Results and Conclusion: Oral administration of CCl4 (1 ml/kg) significantly (P< 0.001) raised the serum levels of liver enzyme markers compared to the normal control group. Pre-treatment with 125, 250, and 500 mg/kg of R. abyssinicus extract reduced the serum level of CCl4-induced rise in liver enzyme markers with the highest reduction observed at a dose of 500 mg/kg. Likewise, in the post-treatment model, the crude extract and butanol fraction at dose 500 mg/kg reduced levels of liver enzymes. Histopathological examinations revealed lesser liver damage of extract-treated mice compared to the toxic (CCl4-treated) controls. The in vitro radical scavenging activity of the different extracts showed concentration-dependent radical scavenging activity. Thus, the results of this study may justify the traditional use of the plant as a hepatoprotective agent.Conclusion: Results of serum biochemical markers and histopathological examinations of CCl4-induced mice models, in the present study, show the hepatoprotective potential of extracts from the rhizome of R. abyssinicus.Keywords: carbon tetrachloride, hepatoprotective, liver disease, Rumex abyssinicus